The Efficacy of Catfish Skin Gelatin (Pangasius djambal) on Soft Tissue Healing of the Rattus norvegicus. - Fredy Mardiyantoro; Lukman Hakim Hidayat; Vira Dwiviasta Ade Ayu; Asma Syahidah Illia; Diva Alenta Arzeti (Odonto : Dental Journal, 2026)
Background: Traumatic ulcers are common oral mucosal lesions causing discomfort, infection, and delayed healing. Conventional therapy is commonly used, but the use of herbal materials is expected to be an affordable and effective alternative therapy. Gelatin was chosen because it is a natural biomaterial rich in amino acids, which play a role in regulating inflammation and tissue regeneration, particularly in influencing the number of macrophages and lymphocytes in the inflammatory phase and fibroblast proliferation. The primary objective was to determine the effect of Pangasius djambal fish skin gelatin on the healing process of traumatic ulcers in Rattus norvegicusMethod: A number of 36 Wistar rats (Rattus norvegicus) were used as research subjects and divided into three main groups based on the treatment and further divided based on the day of the tissue collection. Traumatic ulcers were induced on the lower jaw labial mucosa using thermal trauma. The Negative Control Group (NC) received no treatment, the Positive Control Group (PC) was treated with Aloclair Plus GelTM, while the Treatment Group (T) was treated with 100% Pangasius djambal skin gelatin. Tissue samples were collected on day 3, 5, and 7, followed by hematoxylin-eosin (HE) staining to observe macrophages, lymphocytes, and fibroblasts under a microscope using 400× magnification.Result: Statistical analysis using the One-way ANOVA test showed a significant difference (p < 0.05) in the number of macrophages, lymphocytes, and fibroblasts across all experimental groups. In the treatment group receiving 100% Pangasius djambal skin gelatin, a significant decrease in macrophages and lymphocytes was observed on 5th and 7th days, indicating a faster resolution of the inflammatory phase. Simultaneously, there was a significant increase in the number of fibroblasts from 5th to 7th day in the treatment group compared to the control groups, demonstrating accelerated granulation tissue formation and enhanced wound healing.Conclusion: The recovery of traumatic ulcers in Rattus norvegicus can be affected by application of Pangasius djambal skin gelatin.